Two nuclear loci Rf-m1 and Rf-m2 interplay to determine the fertility restoring efficacy of ZD-type CMS soybean - Xiaoxia Yu; Yupeng Feng; Lulu Zhou; Hongye Gao; Hongbin Wang; Yaru Chen; Jiamai Liang; Tianyu Meng; Meng Li; Yihan Yuan; Junping Yu; Hao Liu; et al. (Theoretical and Applied Genetics, 2025)

The dual-targeted transcription factor BAI1 orchestrates nuclear and plastid gene transcription in land plants - Jing Qin; Yelin Shan; Hao Liu; Zhangzhi Xue; Yike Xie; Guoxin Yuan; Yiming Zou; Xiaonuan Hao; Yunpeng Zhu; Xuan Shen; Meng Li; Xu Wang; et al. (Molecular Plant, 2025)

MS2/GmAMS1 encodes a bHLH transcription factor important for tapetum degeneration in soybean - Junping Yu; Yan Xu; Yuanyuan Huang; Yuxue Zhu; Lulu Zhou; Yunpeng Zhang; Bingyao Li; Hao Liu; Aigen Fu; Min Xu (Plant Cell Reports, 2024)

A single nucleotide polymorphism in an R2R3 MYB transcription factor gene triggers the male sterility in soybean ms6 (Ames1) - Junping Yu; Guolong Zhao; Wei Li; Ying Zhang; Peng Wang; Aigen Fu; Limei Zhao; Chunbao Zhang; Min Xu (Theoretical and Applied Genetics, 2021)
Key message Identification and functional analysis of the male sterile gene MS6 in Glycine max . Abstract Soybean ( Glycine max (L.) Merr . ) is an important crop providing vegetable oil and protein. The male sterility-based hybrid breeding is a promising method for improving soybean yield to meet the globally growing demand. In this research, we identified a soybean genic male sterile locus, MS6 , by combining the bulked segregant analysis sequencing method and the map-based cloning technology. MS6 , highly expressed in anther, encodes an R2R3 MYB transcription factor (GmTDF1-1) that is homologous to Tapetal Development and Function 1, a key factor for anther development in Arabidopsis and rice. In male sterile ms6 (Ames1), the mutant allele contains a missense mutation, leading to the 76th leucine substituted by histidine in the DNA binding domain of GmTDF1-1. The expression of soybean MS6 under the control of the AtTDF1 promoter could rescue the male sterility of attdf1 but ms6 could not. Additionally, ms6 overexpression in wild-type Arabidopsis did not affect anther development. These results evidence that GmTDF1-1 is a functional TDF1 homolog and L76H disrupts its function. Notably, GmTDF1-1 shows 92% sequence identity with another soybean protein termed as GmTDF1-2, whose active expression also restored the fertility of attdf1 . However, GmTDF1-2 is constitutively expressed at a very low level in soybean, and therefore, not able to compensate for the MS6 deficiency. Analysis of the TDF1-involved anther development regulatory pathway showed that expressions of the genes downstream of TDF1 are significantly suppressed in ms6 , unveiling that GmTDF1-1 is a core transcription factor regulating soybean anther development.

A simple and reliable method for creating PCR-detectable mutants in Arabidopsis with the polycistronic tRNA–gRNA CRISPR/Cas9 system - Liangliang Hui; Min Zhao; Junqi He; Yingying Hu; Yanshuang Huo; Houyan Hao; Yaqi Hao; Weining Zhu; Yuhua Wang; Min Xu; Aigen Fu (Acta Physiologiae Plantarum, 2019)
To develop an easy and robust method for creating genetically stable and easily detectable Arabidopsis mutants, we adopted the polycistronic tRNA–gRNA CRISPR/Cas9 (PTG/Cas9) system, a multiplex gene-editing tool in rice, with PTOX as the reporter gene. The PTG/Cas9 system has a great potential in generating large deletions detectable by PCR, which greatly simplifies the laborious work of mutant screening. We constructed a PTOX –PTG/Cas9 system with five gRNAs and introduced it into Arabidopsis . At T1 generation, 24.4% of transgenic plants were chimeric with PCR-detectable deletions in PTOX locus, but no homozygous mutant was found, indicating that gene editing occurred predominantly in somatic cells. After a self-cross propagation, 60% of T1 chimeric plants were able to produce homozygous, heterozygous, or bi-allelic ptox offsprings. Inheritable homozygous ptox mutants without Cas9 gene can be obtained earliest at T2 generation. We further targeted five other genes using the same procedure and achieved homozygous Cas9-free mutants with large deletions for all genes within three generations. We established a standard and reliable protocol to generate stable inherited deletion mutants in 2–3 generations along with simple PCR screening methods. We conclude that the rice PTG/Cas9 system is an efficient, easy, and rapid tool to edit genes in Arabidopsis . We propose that it could be applied to other genes in Arabidopsis , and it might have the potential to edit genes in other plant species as well.

Crystal structure of Psb27 from Arabidopsis thaliana determined at a resolution of 1.85 Å - Cheng Xingxing; Liu Jiuyang; Zhang Huan; Li Fudong; Zhang Shuya; Xu Min; Ruan Ke; Wang Yuhua; Fu Aigen (Photosynthesis Research, 2018)